Stress and Coping Theory: Experiences of Designated Teacher-Counselors Supporting Sexual Violence Victims - Dela Cruz, Delon Angelo L.; Aguilar-Delavin, Elreen; Pautan, Jonnie A. (Future Science / FSH-PH Publications, 2026)
This article examines the experiences of designated teacher-counselors in secondary schools within the Milagros District, focusing on their role in supporting student survivors of sexual violence. The study used narrative inquiry to illustrate how teacher-counselors navigate emotionally charged situations, frequently developing close, sympathetic relationships that put them under psychological stress. One recurrent narrative stood out as emblematic, highlighting the conflict between individual dedication and structural constraints, including poor training, ambiguous function definitions, and minimal institutional support. In the absence of structured mental health services, the analysis exposes how teacher-counselors rely on informal coping mechanisms, challenging widely held beliefs about school-based care. Some contend that although these spontaneous reactions show resiliency, they also highlight the urgent need for official, trauma-informed infrastructure. The study presents deeper concerns about how schools define care roles and how equipped they are to assist those who provide care for others.